L-Shaped-Sensor-Array-Based Localization and Tracking Method for 3D Maneuvering Target - Xing Zhang; Xue Wang (International Journal of Distributed Sensor Networks)
The localization and tracking technology for a three-dimensional target, which is a kernel problem in the military area, has received more and more attention. This paper proposes a closed-loop system to detect 3D maneuvering targets, including data acquisition, the direction of arrival (DOA) estimation, the triangle localization, and a trajectory prediction. This system firstly uses several L-shaped sensor arrays to sample the signals of maneuvering targets. Then the 2D ESPRIT algorithm and a maximum likelihood algorithm are introduced to achieve the positions of the spatial targets. Thirdly an autoregressive (AR) particle filter (PF) algorithm is realized to predict the locations in the next moment. Finally the localization process is directed by using the predicted positions to form a positive feedback closed loop. Experiment results show that this system can enhance the robustness and accuracy of the localization and tracking for three-dimensional maneuvering targets.